(untitled) (Sociologisk Forskning, 2006)
As the representatives of political authority the police are often the targets for protesters’ interventions and their very presence can in turn ‘trigger’ political disorder. In this article I analyze two radically different approaches to the policing of protest: protest policing in conjunction with the EU Summit meetings in Göteborg 2001 and Copenhagen 2002. In what ways are spaces for democratic protest protected, alternatively threatened, by political policing? Unquestionably, direct threats are posed to the public spaces for political protest in the event of serious public disorder and even more seriously in the event of police riots as we witnessed in Gothenburg. A deployment of ‘keystone cops’ in the action spaces of social movement politics risks serious threats to civil liberties, which were the outcomes of a strategy wedded to the control of territorial spaces. Were these ‘democratic spaces’ even endangered by policing measures designed to control situations as was the case in Copenhagen? The tentative answer offered is yes. The threats are of course subtler, but nevertheless, threats to civil and political liberties were incurred. The question of course arises as to whether threats to civil liberties can indeed be wholly eliminated in the quest for public order in present-day risk societies.